Early Detection of Age‐Related Decline of Muscle Cell Mass by Intracellular Water Assessment Compared With MRI or DXA - Akifumi Maeda; Yosuke Yamada; Maito Yamagishi; Yoko Okada; Tsukasa Yoshida; Yuta Otsuka; Takayuki Izumo; Tomohiro Rogi; Hiroshi Shibata; Masahiro Fukuda; Takuma Arimitsu; Naokazu Miyamoto; et al. (Journal of Cachexia, Sarcopenia and Muscle, 2025)
ABSTRACT Background Ageing is commonly associated with a decrease in muscle strength, which is largely linked to decreases in skeletal muscle mass (SMM). The rate of the age‐related decline in muscle strength is different from the rate of the age‐related decline in SMM. Current estimation methods for SMM, such as magnetic resonance imaging (MRI) and dual‐energy x‐ray absorptiometry (DXA), evaluate both intracellular and extracellular water volumes, potentially overestimating atrophied muscle fibres. Recently, segmental bioelectrical impedance spectroscopy (S‐BIS), which distinguishes intracellular water (ICW) associated with muscle cell mass (MCM), has been developed. However, this method has not been sufficiently compared with other SMM assessment methods, especially with respect to age‐related changes. This study was aimed at comparing the age‐related differences in SMM measured by S‐BIS, MRI and DXA over a wide range of ages and to identify the optimal method for evaluating age‐related muscle tissue changes. Methods This cross‐sectional study included 41 women and 43 men living in Japan (mean [SD] age: 53.51 [13.76] years; height: 162.96 [9.16] cm; BMI: 22.32 [2.94]). Three different methods were applied to estimate SMM: leg lean mass was measured via DXA; mid‐thigh muscle cross‐sectional area (CSA) was measured via MRI; and thigh total water, thigh ICW and the ratio of extracellular water to total water (ECW/TW) were measured via S‐BIS. To more effectively compare age‐related differences in each parameter, we normalised the relative values for each participant by using the mean scores for the 30–39‐year group for each parameter. Segmented regression analysis was performed to detect age breaking points for each parameter. Results Each SMM parameter obtained via the different methods markedly decreased with increasing age (p < 0.05). In contrast, the ECW/TW increased with increasing age (p < 0.05). The age breaking points for leg lean mass measured by DXA, mid‐thigh CSA measured by MRI and thigh ICW measured by S‐BIS were 57.7, 56.3 and 43.2 years, respectively (p < 0.05). Conclusions Compared with DXA or MRI, S‐BIS was found to be more sensitive for detecting age‐related SMM decrease at earlier stages. S‐BIS can distinguish between ICW and ECW, providing a more accurate estimation of MCM that is linked to muscle contractions. This study offers new insights that SMM begins to decrease in the 50s, while MCM does in the early 40s. These findings emphasise the need to address the age‐related decline in MCM starting in the early 40s to prevent a decrease in the quality of life of older individuals.